Effects of static and progressively increasing prey density regimens on larval performance of largemouth bass (Micropterus nigricans) reared in an intensive recirculating aquaculture system - Nelson S. Parajuli; Robert Glennon; Anneleen Swanepoel; Dustin Goodman; Josh Sakmar; Allen Nicholls; Luke A. Roy; D. Allen Davis; Timothy J. Bruce; Ian A.E. Butts (Aquaculture, 2027)

Impact of light intensity and tank color on growth and development of largemouth bass, Micropterus nigricans, during early life history - Anneleen Swanepoel; Nelson S. Parajuli; Kaylan Martin; Kyle R. Wood; Josh Sakmar; Allen Nicholls; Anita M. Kelly; Luke A. Roy; Timothy J. Bruce; D. Allen Davis; Ian A.E. Butts (Aquaculture, 2026)

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Predator and prey density effects on early life-history performance of largemouth bass (Micropterus nigricans) in an indoor recirculating aquaculture system - Nelson S. Parajuli; Josh Sakmar; Allen Nicholls; Anita M. Kelly; Luke A. Roy; D. Allen Davis; Timothy J. Bruce; Matthew K. Litvak; Ian A.E. Butts (Aquaculture, 2026)

Lead and other Trace Elements in Spices in the Las Vegas Market: Human Health Risk Assessment - Douglas B. Sims; Desta Woldetsadik; Joshua R. Monk; Mark C. Garner; Christopher Adcock; Emmanuel Herrera Huerta; Timothy Nelson; Amanda C. Hudson (Biological Trace Element Research, 2026)

Evaluating bidirectional, longitudinal associations between adolescent executive control and eating behaviors - Hope Thilges; Eric M. Phillips; Emily L. Goldberg; Rebecca L. Brock; Katherine M. Kidwell; Amy Lazarus Yaroch; Jennie L. Hill; Kimberly Andrews Espy; Jennifer Mize Nelson; W. Alex Mason; Timothy D. Nelson (Appetite, 2026)

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Examining longitudinal associations between early environmental deprivation and unpredictability and dietary quality and eating behaviors a decade later - Emily L. Goldberg; Rebecca L. Brock; Amy Lazarus Yaroch; Jennie L. Hill; W. Alex Mason; Jennifer Mize Nelson; Kimberly Andrews Espy; Timothy D. Nelson (Appetite, 2026)

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Environmental identities of college students reveal potential conflicts and common ground for wildlife conservation - Richard Von Furstenberg; Lincoln R. Larson; M. Nils Peterson; Kangjae Jerry Lee; Victoria R. Vayer; kathryn stevenson; Stacy A.C. Nelson; Jeremy Bruskotter; Adam A. Ahlers; Christine Anhalt-Depies; Taniya Bethke; Chris Chizinski; et al. (Biological Conservation, 2025)

Synergistic use of Sentinel-1 and Sentinel-2 data for Fall Armyworm infestation detection and mapping in maize croplands - Tatenda Dzurume; Roshanak Darvishzadeh; Timothy Dube; T.S Amjath Babu; Mutasim Billah; Syed Nurul Alam; Mustafa Kamal; Md. Harun-Or-Rashid; Badal Chandra Biswas; Md. Ashraf Uddin; Md. Abdul Muyeed; Md. Mostafizur Rahman Shah; et al. (International Journal of Remote Sensing, 2025)

Longitudinal Associations Between Adolescent Electronic Cigarette Use and Eating Behaviors - Saira Sarwar; W. Alex Mason; Timothy Nelson (Journal of Nutrition Education and Behavior, 2025)

Impact of a Consumer Farmers Market App on SNAP Transactions and Nutrition Incentive Use Are Farmers Markets in Ohio - Owusua Yamoah; Timothy Ciesielski; Emily Nelson; Shannon Walker; Kathryn Poppe; Darcy Freedman (Journal of Nutrition Education and Behavior, 2025)

Mineral profile of infant formula in the Las Vegas market: Compliance with label and regulations, contribution to dietary reference intakes and method comparison - Desta Woldetsadik; Douglas B. Sims; Emmanuel Herrera Huerta; Timothy Nelson; Abigael Walker; Joshua Monk; Mark C. Garner; Christopher Adcock; Amanda C. Hudson; David E.B. Fleming (Food and Chemical Toxicology, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Associations Between Adolescent Food Environments and Dietary Intake - Saira Sarwar; Jennie L. Hill; Amy Lazarus Yaroch; Jennifer Mize Nelson; Kimberly Andrews Espy; Timothy D. Nelson (Journal of Nutrition Education and Behavior, 2024)

Disentangling the veil line for Brazilian biodiversity: An overview from two long-term research programs reveals huge gaps in ecological data reporting - Aretha Franklin Guimaraes; Luciano Carramaschi de Alagao Querido; Taina Rocha; Domingos de Jesus Rodrigues; Pedro Lage Viana; Helena de Godoy Bergallo; Geraldo Wilson Fernandes; Tiago Shizen Pacheco Toma; Helena Streit; Gerhard Ernst Overbeck; Alberico Queiroz Salgueiro de Souza; Albertina Pimentel Lima; et al. (Science of The Total Environment, 2024)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Elemental profile of wheat in the las vegas market: Geographic origin discrimination and probabilistic health risk assessment - Desta Woldetsadik; Douglas B. Sims; Emmanuel Herrera Huerta; Timothy Nelson; Mark C. Garner; Joshua Monk; Amanda C. Hudson; Kristian Schlick (Food and Chemical Toxicology, 2024)

New Oldowan locality Sare-Abururu (ca. 1.7 Ma) provides evidence of diverse hominin behaviors on the Homa Peninsula, Kenya - Emma M. Finestone; Thomas W. Plummer; Thomas H. Vincent; Scott A. Blumenthal; Peter W. Ditchfield; Laura C. Bishop; James S. Oliver; Andy I.R. Herries; Christopher Vere Palfery; Timothy P. Lane; Elizabeth McGuire; Jonathan S. Reeves; et al. (Journal of Human Evolution, 2024)

Food system resilience measurement: principles, framework and caveats - Christophe Béné; Timothy R. Frankenberger; Suzanne Nelson; Mark Alexander Constas; Gregory Collins; Mark Langworthy; Karyn Fox (Food Security, 2023)
There is growing recognition that a better understanding of how food systems respond to crises is critical to build and protect the food security of local populations. But rigorous and reliable methods to measure food system resilience are still missing. In this paper, we build on the current literature to develop an analytical framework aimed at assessing the resilience of food systems at local level. The novel element of the analysis lies in the levels at which resilience is considered. Combining the individual actor level with the notion of 'emergent properties' of food systems, we argue that the overall resilience of food system results from processes that take place – and need to be measured – at both individual and system levels. The framework is structured around three components: (i) the mapping of the actors and the local food system; (ii) the assessment of the resilience of these actors and that of the food system, and (iii) the outcomes of this resilience, assessed in term of local population’s food security. For each of those components, indicators are proposed and the ways to collect them are discussed. The paper then presents the types of analyses that would be necessary to complete to gain a better understanding of the situation regarding the resilience of the local food system under consideration, including the analysis of “positive deviance” among food system actors. The paper concludes with a series of reflections about the caveats and challenges that one may face when attempting to assess food system resilience.

Drivers of habitat availability for terrestrial mammals: Unravelling the role of livestock, land conversion and intrinsic traits in the past 50 years - Michela Pacifici; Andrea Cristiano; Maria Lumbierres; Mauro Lucherini; David Mallon; Erik Meijaard; Sergio Solari; Marcelo F. Tognelli; Jerrold L. Belant; Thomas M. Butynski; Drew Cronin; Jean‐Pierre d'Huart; et al. (Global Change Biology, 2023)
The global decline of terrestrial species is largely due to the degradation, loss and fragmentation of their habitats. The conversion of natural ecosystems for cropland, rangeland, forest products and human infrastructure are the primary causes of habitat deterioration. Due to the paucity of data on the past distribution of species and the scarcity of fine‐scale habitat conversion maps, however, accurate assessment of the recent effects of habitat degradation, loss and fragmentation on the range of mammals has been near impossible. We aim to assess the proportions of available habitat within the lost and retained parts of mammals' distribution ranges, and to identify the drivers of habitat availability. We produced distribution maps for 475 terrestrial mammals for the range they occupied 50 years ago and compared them to current range maps. We then calculated the differences in the percentage of ‘area of habitat’ (habitat available to a species within its range) between the lost and retained range areas. Finally, we ran generalized linear mixed models to identify which variables were more influential in determining habitat availability in the lost and retained parts of the distribution ranges. We found that 59% of species had a lower proportion of available habitat in the lost range compared to the retained range, thus hypothesizing that habitat loss could have contributed to range declines. The most important factors negatively affecting habitat availability were the conversion of land to rangeland and high density of livestock. Significant intrinsic traits were those related to reproductive timing and output, habitat breadth and medium body size. Our findings emphasize the importance of implementing conservation strategies to mitigate the impacts caused by human activities on the habitats of mammals, and offer evidence indicating which species have the potential to reoccupy portions of their former range if other threats cease to occur.

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Distinct fungal and bacterial responses to fire severity and soil depth across a ten-year wildfire chronosequence in beetle-killed lodgepole pine forests - Marcos V. Caiafa; Amelia R. Nelson; Thomas Borch; Holly K. Roth; Timothy S. Fegel; Charles C. Rhoades; Michael J. Wilkins; Sydney I. Glassman (Forest Ecology and Management, 2023)

Analyzing the impact and evolution of ocean & coastal management: 30 years in retrospect - Jihong Chen; Hao Chen; Timothy F. Smith; Nelson Rangel-Buitrago (Ocean & Coastal Management, 2023)

Corrigendum: Associations between cyanobacteria and indices of secondary production in the western basin of Lake Erie - James H. Larson; Mary Anne Evans; Robert J. Kennedy; Sean W. Bailey; Keith A. Loftin; Zachary R. Laughrey; Robin A. Femmer; Jeff S. Schaeffer; William B. Richardson; Timothy T. Wynne; J. C. Nelson; Joseph W. Duris (Limnology and Oceanography, 2022)
In the last year, we became aware that data used in our above‐referenced manuscript from 2018 published in Limnology and Oceanography contained significant errors. In the 2018 manuscript, we found that indices of secondary production were negatively correlated to indices of cyanobacterial abundance and toxicity. Unfortunately, one of our indices of cyanobacterial abundance (biovolume) and our measurement of toxicity (microcystin concentration) were inaccurate in the data we used in the 2018 manuscript. Upon discovering these errors, we immediately began correcting the repositories where these data were available. Having corrected those data repositories, we are now reporting on the re‐analysis of the data using the methods previously described in the 2018 manuscript. Although the relationships are slightly different, our interpretation is that the conclusions of the 2018 manuscript are still valid using the corrected data. The data errors we experienced were traced to a spreadsheet that was used to share data among the research team, which had errors caused by mistakes in copy‐pasting formulas instead of data and ‘inadvertent’ edits that were saved by the spreadsheet's auto‐save function. We apologize to the scientific community for these errors.

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

ACMT Position Statement: Caring for Patients with Opioid Use Disorder during Coronavirus Disease Pandemic - Andrew Stolbach; Maryann Mazer-Amirshahi; Evan S. Schwarz; David Juurlink; Timothy J. Wiegand; Lewis S. Nelson (Journal of Medical Toxicology, 2020)

Microbial tropicalization driven by a strengthening western ocean boundary current - Lauren F. Messer; Martin Ostrowski; Martina A. Doblin; Katherina Petrou; Mark E. Baird; Timothy Ingleton; Andrew Bissett; Jodie Van de Kamp; Tiffanie Nelson; Ian Paulsen; Levente Bodrossy; Jed A. Fuhrman; et al. (Global Change Biology, 2020)
Western boundary currents (WBCs) redistribute heat and oligotrophic seawater from the tropics to temperate latitudes, with several displaying substantial climate change‐driven intensification over the last century. Strengthening WBCs have been implicated in the poleward range expansion of marine macroflora and fauna, however, the impacts on the structure and function of temperate microbial communities are largely unknown. Here we show that the major subtropical WBC of the South Pacific Ocean, the East Australian Current (EAC), transports microbial assemblages that maintain tropical and oligotrophic ( k ‐strategist) signatures, to seasonally displace more copiotrophic ( r ‐strategist) temperate microbial populations within temperate latitudes of the Tasman Sea. We identified specific characteristics of EAC microbial assemblages compared with non‐EAC assemblages, including strain transitions within the SAR11 clade, enrichment of Prochlorococcus , predicted smaller genome sizes and shifts in the importance of several functional genes, including those associated with cyanobacterial photosynthesis, secondary metabolism and fatty acid and lipid transport. At a temperate time‐series site in the Tasman Sea, we observed significant reductions in standing stocks of total carbon and chlorophyll a , and a shift towards smaller phytoplankton and carnivorous copepods, associated with the seasonal impact of the EAC microbial assemblage. In light of the substantial shifts in microbial assemblage structure and function associated with the EAC, we conclude that climate‐driven expansions of WBCs will expand the range of tropical oligotrophic microbes, and potentially profoundly impact the trophic status of temperate waters.

Storage of orchid pollinia with varying lipid thermal fingerprints - Ceci Castilho Custodio; Nelson B. Machado-Neto; Rodrigo B. Singer; Hugh W. Pritchard; Philip T. Seaton; Timothy R. Marks (Protoplasma, 2020)

Leadership Roles in Opioid Stewardship and the Treatment of Patients with Opioid Use Disorder Among Medical Toxicologists - Joseph E. Carpenter; Brian Patrick Murray; Maryann Mazer-Amirshahi; JoAn R. Laes; Nicholas Nacca; Lewis S. Nelson; Jeanmarie Perrone; Evan S. Schwarz; Timothy J. Wiegand; Paul M. Wax (Journal of Medical Toxicology, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

ACMT Position Statement: Remove the Waiver Requirement for Prescribing Buprenorphine for Opioid Use Disorder - Ryan Marino; Jeanmarie Perrone; Lewis S. Nelson; Timothy J. Wiegand; Evan S. Schwarz; Paul M. Wax; Andrew I. Stolbach (Journal of Medical Toxicology, 2019)

Cerebral blood flow in acute concussion: preliminary ASL findings from the NCAA-DoD CARE consortium - Yang Wang; Andrew S. Nencka; Timothy B. Meier; Kevin Guskiewicz; Jason P. Mihalik; M. Alison Brooks; Andrew J. Saykin; Kevin M. Koch; Yu-Chien Wu; Lindsay D. Nelson; Thomas W. McAllister; Steven P. Broglio; et al. (Brain Imaging and Behavior, 2019)

ACMT Position Statement: Buprenorphine Administration in the Emergency Department - Paul M. Wax; Andrew I. Stolbach; Evan S. Schwarz; Brandon J. Warrick; Timothy J. Wiegand; Lewis S. Nelson (Journal of Medical Toxicology, 2019)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Associations between cyanobacteria and indices of secondary production in the western basin of Lake Erie - James H. Larson; Mary Anne Evans; Robert J. Kennedy; Sean W. Bailey; Keith A. Loftin; Zachary R. Laughrey; Robin A. Femmer; Jeff S. Schaeffer; William B. Richardson; Timothy T. Wynne; J. C. Nelson; Joseph W. Duris (Limnology and Oceanography, 2018)
Large lakes provide a variety of ecological services to surrounding cities and communities. Many of these services are supported by ecological processes that are threatened by the increasing prevalence of cyanobacterial blooms which occur as aquatic ecosystems experience cultural eutrophication. Over the past 10 yr, Lake Erie experienced cyanobacterial blooms of increasing severity and frequency, which have resulted in impaired drinking water for the surrounding communities. Cyanobacterial blooms may impact ecological processes that support other services, but many of these impacts have not been documented. Secondary production (production of primary consumers) is an important process that supports economically important higher trophic levels. Cyanobacterial blooms may influence secondary production because cyanobacteria are a poor‐quality food resource and cyanotoxins may be harmful to consumers. Over 3 yr at 34 sites across the western basin of Lake Erie, we measured three indices of secondary production that focus on the dominant bivalve taxa: (1) growth of a native unionid mussel, (2) the size of young‐of‐year dreissenid mussels, and (3) the mass of colonizing animals on a Hester‐Dendy sampler. Associations between these indices and cyanobacterial data were estimated to assess whether cyanobacteria are associated with variation in secondary production in the western basin of Lake Erie. The results suggest cyanobacterial abundance alone is only weakly associated with secondary production, but that cyanotoxins have a larger effect on secondary production. Given recurring late‐summer cyanobacterial blooms, this impact on secondary production has the potential to undermine Lake Erie's ability to sustain important ecosystem services.

High Energy or Protein Concentrations in Food as Possible Offsets for Cyanide Consumption by Specialized Bamboo Lemurs in Madagascar - Timothy M. Eppley; Chia L. Tan; Summer J. Arrigo-Nelson; Giuseppe Donati; Daniel J. Ballhorn; Jörg U. Ganzhorn (International Journal of Primatology, 2017)

Subduction initiation and ophiolite crust: new insights from IODP drilling - Mark K. Reagan; Julian A. Pearce; Katerina Petronotis; Renat R. Almeev; Aaron J. Avery; Claire Carvallo; Timothy Chapman; Gail L. Christeson; Eric C. Ferré; Marguerite Godard; Daniel E. Heaton; Maria Kirchenbaur; et al. (International Geology Review, 2017)

Patterns and mechanisms of invasive plant impacts on North American birds: a systematic review - Scott B. Nelson; Jaime J. Coon; Courtney J. Duchardt; Jason D. Fischer; Samniqueka J. Halsey; Adam J. Kranz; Christine M. Parker; Sarah C. Schneider; Timothy M. Swartz; James R. Miller (Biological Invasions, 2017)

Compound heterozygous NOTCH1 mutations underlie impaired cardiogenesis in a patient with hypoplastic left heart syndrome - Jeanne L. Theis; Sybil C. L. Hrstka; Jared M. Evans; Megan M. O’Byrne; Mariza de Andrade; Patrick W. O’Leary; Timothy J. Nelson; Timothy M. Olson (Human Genetics, 2015)

A spectral model for estimating temporal and spatial evolution of rippled seabeds - Timothy R. Nelson; George Voulgaris (Ocean Dynamics, 2015)

A Review of Methods for Determining the Long Term Behavior of Endovascular Devices - Brónadh Lynch; John Nelson; Eamon G. Kavanagh; Stewart R. Walsh; Timothy M. McGloughlin (Cardiovascular Engineering and Technology, 2014)

Mercury in bats from the northeastern United States - David E. Yates; Evan M. Adams; Sofia E. Angelo; David C. Evers; John Schmerfeld; Marianne S. Moore; Thomas H. Kunz; Timothy Divoll; Samuel T. Edmonds; Christopher Perkins; Robert Taylor; Nelson J. O’Driscoll (Ecotoxicology, 2014)

Characterization of Recombinant Human IL-15 Deamidation and Its Practical Elimination through Substitution of Asparagine 77 - David F. Nellis; Dennis F. Michiel; Man-Shiow Jiang; Dominic Esposito; Richard Davis; Hengguang Jiang; Angela Korrell; George C. Knapp; Lauren E. Lucernoni; Roy E. Nelson; Emily M. Pritt; Lauren V. Procter; et al. (Pharmaceutical Research, 2012)

Improved assessment of viability and germination of Cattleya (Orchidaceae) seeds following storage - Silvério Takao Hosomi; Ceci Castilho Custódio; Philip T. Seaton; Timothy R. Marks; Nelson Barbosa Machado-Neto (In Vitro Cellular & Developmental Biology - Plant, 2012)

Forcing and Dynamics of Seafloor-Water Column Exchange on a Broad Continental Shelf - William Savidge; Ann Gargett; Richard Jahnke; James Nelson; Dana Savidge; R. Timothy Short; George Voulgaris (Oceanography, 2008)

Regression Estimation Following the Square-Root Transformation of the Response - Timothy G. Gregoire; Qi Feng Lin; Johnathan Boudreau; Ross Nelson (Forest Science, 2008)
In a variety of regression situations, there is interest in predicting the value of Y2, yet it is useful to model it using a square root transformation, such that Y rather than Y2 is regressed on one or more covariates. The back-transformation bias of the square root transformation of the response variable of interest is presented in detail. An unbiased estimator is presented: . Its performance is compared against that of two biased estimators: and . The first two moments of these estimators are derived analytically and verified by means of a simulation study. Both biased estimators have lower mean square errors than the unbiased estimator. An example wherein aboveground biomass is the response variable is presented for illustration.

ECOLOGICAL AND PHYSIOLOGICAL CONTROLS OF SPECIES COMPOSITION IN GREEN MACROALGAL BLOOMS - Timothy A. Nelson; Karalon Haberlin; Amorah V. Nelson; Heather Ribarich; Ruth Hotchkiss; Kathryn L. Van Alstyne; Lee Buckingham; Dejah J. Simunds; Kerri Fredrickson (Ecology, 2008)
Green macroalgal blooms have substantially altered marine community structure and function, specifically by smothering seagrasses and other primary producers that are critical to commercial fisheries and by creating anoxic conditions in enclosed embayments. Bottom‐up factors are viewed as the primary drivers of these blooms, but increasing attention has been paid to biotic controls of species composition. In Washington State, USA, blooms are often dominated by Ulva spp. intertidally and Ulvaria obscura subtidally. Factors that could cause this spatial difference were examined, including competition, grazer preferences, salinity, photoacclimation, nutrient requirements, and responses to nutrient enrichment. Ulva specimens grew faster than Ulvaria in intertidal chambers but not significantly faster in subtidal chambers. Ulva was better able to acclimate to a high‐light environment and was more tolerant of low salinity than Ulvaria. Ulvaria had higher tissue N content, chlorophyll, chlorophyll b : chlorophyll a , and protein content than Ulva. These differences suggest that nitrogen availability could affect species composition. A suite of five grazers preferred Ulva to Ulvaria in choice experiments. Thus, bottom‐up factors allow Ulva to dominate the intertidal zone while resistance to grazers appears to allow Ulvaria to dominate the subtidal zone. While ulvoid algae are in the same functional‐form group, they are not functionally redundant.

Spatial variation in dimethylsulfoniopropionate (DMSP) production in Ulva lactuca (Chlorophyta) from the Northeast Pacific - Kathryn L. Van Alstyne; Lauren Koellermeier; Timothy A. Nelson (Marine Biology, 2007)

RTS, a rice anther-specific gene is required for male fertility and its promoter sequence directs tissue-specific gene expression in different plant species - Hong Luo; Jang-Yong Lee; Qian Hu; Kimberly Nelson-Vasilchik; Timothy K. Eitas; Colin Lickwar; Albert P. Kausch; Joel M. Chandlee; Thomas K. Hodges (Plant Molecular Biology, 2006)

Corporate Environmental Management Program at the University of Minnesota - Sangwon Suh; Timothy Smith; Casey Nelson; Shri Ramaswamy (The International Journal of Life Cycle Assessment, 2005)

A Population Pharmacokinetic Analysis of Milrinone in Pediatric Patients After Cardiac Surgery - James M. Bailey; Timothy M. Hoffman; David L. Wessel; David P. Nelson; Andrew M. Atz; Anthony C. Chang; Thomas J. Kulik; Thomas L. Spray; Akbar Akbary; Richard P. Miller; Gil Wernovsky (Journal of Pharmacokinetics and Pharmacodynamics, 2004)

The Use of Seasonal Climate Forecasting in Policymaking: Lessons from Northeast Brazil - Maria Carmen Lemos; Timothy J. Finan; Roger W. Fox; Donald R. Nelson; Joanna Tucker (Climatic Change, 2002)

Maize C4 and non-C4 NADP-dependent malic enzymes are encoded by distinct genes derived from a plastid-localized ancestor - S. Lorraine Tausta; Heather Miller Coyle; Beverly Rothermel; Virginia Stiefel; Timothy Nelson (Plant Molecular Biology, 2002)

Identification and mapping of a putative stress response regulator gene in barley - Marina Malatrasi; Timothy J. Close; Nelson Marmiroli (Plant Molecular Biology, 2002)

The Effects of Fixed-Area Plot Width on Forest Canopy Height Simulation - Ross F. Nelson; Timothy G. Gregoire; Richard G. Oderwald (Forest Science, 1998)
Mapped-stand data which includes tree location and mensuration data may be used to simulate the height characteristics of a forest canopy in a computer. The dimensions of the rectangular, fixed-area ground plot which is used to collect the tree location and mensuration data can profoundly affect the accuracy of the resultant computer reconstruction of forest canopy heights. Thin fixed-area plots result in forest canopy height constructs (i.e., canopy height models, or CHMs) which are shorter and less dense than the actual forest stand. Ninety-nine 0.405 ha forest stands in the southeastern and south central United States were analyzed. For each stand, a top-of-canopy height model was generated for the entire stand on a 0.25 m x 0.25 m grid. The mean canopy height and the canopy density of the simulated stand was calculated. A Monte Carlo simulator established randomly located sample plots of varying plot width (1 m to 20 m) at three different sampling intensities (1%, 5%, and 10% of stand area) in the mapped stand. The trees selected on any particular plot were used to generate a CHM, and the sample mean canopy height and canopy density were compared with the corresponding stand values. Samples collected using 1 m wide plots resulted in height models which underestimated average canopy height and canopy closure with deviations greater than 5% of the stand value, 95-100% of the time. The underestimation results from the construction of top-of-canopy architecture based on measurements of crowns belonging only to trees whose boles are within the plot. This construction technique omits crowns extending over the plot belonging to tree boles located off the plot. Thinner plots tend to miss more of the trees which support the canopy over the plot. For the 99 stands considered in this study, ground plot widths on the order of 6 to 8 m were required in order to acquire ground data which could be used to accurately model forest canopy height characteristics. The minimum ground plot width required to produce an accurate height model decreased with increasing stem density; a plot width of 4 m, for instance, may be used at stem densities of ~2000 stems ha-1. For. Sci. 44(3):438-444.